Children’s digital practices and family dynamics during the COVID-19 lockdown: contrasting children’s and parents’ perspectives - Matsumoto, Mitsuko; Vilaboa, Clara; Aliagas, Cristina; Correro Iglesias, Cristina; Espallargas Carvajal, Loreto Alejandra (Journal of Family Studies, 2024)
Since 2020, research has continued to grow on children’s digital practices during the COVID-19 lockdown, but the child’s perspective has commonly been ignored. This article aims to depict how the COVID-19 lockdown altered family dynamics regarding the use of technology, focusing on screen media. In particular, it illustrates how parents and children acted upon these changes, managing and negotiating children’s digital practices during the circumstances. As part of a larger European study, we have carried out online interviews with 10 Spanish families with children between 6 and 12 years of age. We conducted interviews both with children and adults, complementing and dynamizing them with other instruments (questionnaires and activity sheets). The study demonstrates that both children and parents are active agents in the family dynamics around the use of technology. Children have their own perspectives and expectations about technology, which do not necessarily coincide with their parents’. Furthermore, this study shows the diversity of strategies devised by the families to manage children’s digital practices, as well as to deal with the tensions that arose through the differences in perspectives and expectations during the COVID-19 pandemic.
Keywords: digital practices; home; COVID-19; parental mediation; primary school children; Scopus; JCR